1998
DOI: 10.1212/wnl.51.2.447
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation for ischemic stroke and intracerebral hemorrhage

Abstract: MV in acute stroke is associated with high mortality. Mortality and outcome were similar for ISCH and HEM; however, the factors predictive of outcome may differ and influence decisions about the use of MV in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
99
2
9

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(119 citation statements)
references
References 3 publications
9
99
2
9
Order By: Relevance
“…20 before a diagnosis or prognosis can be defi ned. 8 Conversely, patients with many medical and some surgical diagnoses are more likely to have chronic comorbid illnesses related to their ICU admission. One prior study found that nurses rated quality of dying higher for neurology and neurosurgery patients than patients of other specialties.…”
Section: Variables Of Interest Outcome Measuresmentioning
confidence: 99%
“…20 before a diagnosis or prognosis can be defi ned. 8 Conversely, patients with many medical and some surgical diagnoses are more likely to have chronic comorbid illnesses related to their ICU admission. One prior study found that nurses rated quality of dying higher for neurology and neurosurgery patients than patients of other specialties.…”
Section: Variables Of Interest Outcome Measuresmentioning
confidence: 99%
“…Apart from having a higher risk of death, those who survive are frequently left with various degrees of functional and cognitive limitations. [2][3][4][5][6][7][8] Only a small number of specific interventions have been definitively demonstrated in large randomized controlled trials to improve outcomes in neurocritical care. [9][10][11][12][13][14] Many of the treatments that are recommended in consensus guidelines and incorporated into protocols are, by necessity, based on low-quality evidence derived largely from observational studies.…”
Section: Résumémentioning
confidence: 99%
“…Thus, the sum of individual diagnoses exceeds the total number of patients for a particular time period 3 Number of patients with missing data for variables: age (4); sex (0); Glasgow Coma Scale (12); APACHE II (24) reduction in the odds of hospital death from one time period to the next (Table 3). This association persisted with inclusion of the modified APACHE II score in the model as a potential confounder, rather than considering it to be an intermediate variable (OR 0.77, 95% CI 0.60 to 0.98, P = 0.03).…”
Section: Multivariable Analysismentioning
confidence: 99%
“…Thirty percent of those with supratentorial ICH and the majority with cerebellar or brainstem ICH require intubation for airway protection [55]. Intubation can prevent aspiration and maximize oxygenation, but these benefits should be weighed against potential risks of intubation in the acute phase [56].…”
Section: Airway Protectionmentioning
confidence: 99%